Analysis of Students' Scientific Literacy Ability in Terms of Learning Styles on Acid-Base Material - Septiani, Nurul Ulya; Ardhana, Ivan Ashif (IJCER (International Journal of Chemistry Education Research), 2025)
This study aims to determine students' science literacy abilities, to know students' science literacy abilities based on learning styles, and to determine differences in students' science literacy based on learning styles in acid-base materials. This research is a non-experimental causal-comparative quantitative study with a sample of 62 students from 11th grade Science (MIPA) at MAN 1 Jombang, specifically classes XI-H and XI-I. The sample was selected using a purposive sampling techniques. The research instruments used were interviews for the preliminary study, a test consisting of 19 questions covering all literacy indicators with a test reliability score of 0.697, which is considered high, and a questionnaire to determine students' learning styles using the AkuPintar website. The interview results indicate that the school has implemented the independent curriculum, but the application of science literacy in learning is still limited to providing introductory readings before explaining the material and during practice exercises, and has not fully integrated the aspects of science literacy. The research results show that students' science literacy skills on acid-base materials fall into the medium category. Based on science literacy indicators, the high category is found in the indicators of researching, evaluating, and using scientific information for decision-making and action; the medium category is found in the indicator of explaining phenomena scientifically; and the high category is found in the indicators of designing and evaluating designs for scientific investigations and critically interpreting scientific data and evidence. Based on learning styles, students with a visual learning style have higher science literacy skills, followed by students with an auditory learning style and students with a kinesthetic learning style. Although there are differences in mean scores between learning styles, statistically no significant difference was found in students' science literacy abilities based on learning style. This indicates that efforts to improve science literacy should focus on enhancing the quality of teaching, student engagement, and strengthening scientific thinking skills, rather than solely on adapting teaching methods to specific learning styles.